2015
DOI: 10.3233/jad-150099
|View full text |Cite
|
Sign up to set email alerts
|

Additive Impairment of Synaptic Signaling in Cultured Cortical Neurons by Exogenously-Applied Oligomerized Amyloid-β and Airborne Nanoparticles Generated during Photocopying

Abstract: Photocopying in offices and printing centers releases nanoparticles that can reach the brain following inhalation. We examined whether subcytotoxic levels of airborne photocopy-emitted nanoparticles could potentiate perturbation of synaptic signaling in cultured neurons following exposure to amyloid-β (Aβ). Signaling was only transiently inhibited by Aβ or nanoparticles individually, but remained statistically reduced in cultures receiving both after 24 h. In vitro and in vivo studies with copier emitted nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Since NP from TPE represent a complex mixture, containing a large organic component, a sizeable amount of metal oxides, and other more volatile organics absorbed onto surface of PM, the toxicological testing framework for these particles should be expanded to evaluate other organ systems and endpoints-including but not limited to those related to cardiovascular, neurological, and blood systems. For example, Lee et al (2015) demonstrated a concentration-dependent inhibition of synaptic signaling by photocopy center NP in mouse cultured cortical neurons over 0.1-50 μg/mL of administered concentrations (corresponding to delivered concentrations of 0.2-10 μg/mL at 24 hour after taking into account dispersion and dosimetry modeling), and a synergistic effect between amyloid beta and NP. Equally important is utilization of screening assays to understand the impact of variability in chemical composition on toxicity, synergistic effects between organics and metals, and biokinetics of such particles from real world exposures, studies yet to be conducted.…”
Section: Resultsmentioning
confidence: 99%
“…Since NP from TPE represent a complex mixture, containing a large organic component, a sizeable amount of metal oxides, and other more volatile organics absorbed onto surface of PM, the toxicological testing framework for these particles should be expanded to evaluate other organ systems and endpoints-including but not limited to those related to cardiovascular, neurological, and blood systems. For example, Lee et al (2015) demonstrated a concentration-dependent inhibition of synaptic signaling by photocopy center NP in mouse cultured cortical neurons over 0.1-50 μg/mL of administered concentrations (corresponding to delivered concentrations of 0.2-10 μg/mL at 24 hour after taking into account dispersion and dosimetry modeling), and a synergistic effect between amyloid beta and NP. Equally important is utilization of screening assays to understand the impact of variability in chemical composition on toxicity, synergistic effects between organics and metals, and biokinetics of such particles from real world exposures, studies yet to be conducted.…”
Section: Resultsmentioning
confidence: 99%
“…A different class of environmental factors includes air quality/airborne contaminants. Airborne carbon nanoparticles of the sort emitted by standard photocopiers impaired complex synaptic signaling in cortical cultures and furthermore imparted an additive impact to that of Aβ at concentrations at which neither agent perturbed signaling alone [ 56 ]. Comparison of the geographical distribution of individuals with dementia or MCI as reported by the National Alzheimer’s Coordinating Center with ambient air concentrations of ozone and fine particulate matter (PM) suggested that ozone but not PM was associated with more rapid cognitive decline [ 57 ].…”
Section: What Are Some Upstream Events Contributing To Ad?mentioning
confidence: 99%